Magnolia sanchez-vegae, a new species of Magnoliaceae from northern Peru - Peña, José Luis Marcelo; Tomazello Filho, Mario (Phytotaxa, 2014)
The family Magnoliaceae Jussieu (1789: 280) in South America includes a total of 50 species. Thirty species are listed for Colombia, ten for Ecuador, eight for Peru, three each for Brazil and Venezuela, and one for Bolivia (Lozano-Contreras, 1994; Nee, 1994; Dillon & Sanchez, 2009; Arroyo & Pérez 2013; Marcelo-Peña & Arroyo 2013; Vázquez et al. 2013). The following species are currently known to occur in Peru: Magnolia rimachii (Lozano 1994: 104) Govaerts (1996: 71), M. amazonica (Ducke 1915: 11) Govaerts (1996: 70), M. bankardiorum Dillon & Sánchez-Vega (2009: 7), M. jaenensis Marcelo-Peña (2013: 110), M. manguillo Marcelo-Peña & Arroyo (2013: 113), M. elfina Vázquez (2012: 100), M. gentryi Vázquez (2012: 104) and M. peruviana Vázquez.(2012: 117).